Typological Parameters for the Lexica-syntactic Structures of High-digit Numerical Expressions - Luo, Cheng (Linguistica Atlantica, 2000)
The objective of this paper is to explore the lexico-syntactic structure of high-digit numerical expressions (henceforth HDNEs), normally with 4 digits and more, and to propose a set of typological parameters to account for crosslinguistic variations in lexicalization sites. The two parameters of pivot/ anchor and increment are proposed to describe and account for lexicalization sites of HDNEs, with language-specific valuesetting explaining crosslinguistic variation. Support for this analysis includes psycholinguistic evidence from second language acquisition.